FREQUENCY OF THYROID DISORDERS IN TYPE 1 DIABETIC PATIENTS PRESENTING AT JINNAH HOSPITAL, LAHORE. - Nasir Mahmood; Shahbaz Ahmed; Saeed Ahmed (Journal of University Medical & Dental College, 2018)
ABSTRACT:OBJECTIVE: To assess the frequency of thyroid dysfunction either subclinical or overt and autoimmunity of thyroid, in patients having type 1 diabetes. STUDY DESIGN: Cross sectional study. DURATION OF STUDY: This study was carried out from January 2013 to July 2013 at Diabetes/Endocrine clinic of Jinnah Hospital, Lahore. PATIENTS AND METHODS: A total 50 diagnosed cases of type 1 diabetes mellitus of either age and both genders using insulin since diagnosis were selected with non probability purposive sampling technique. Patients were screened for thyroid disease by antithyroid peroxides antibody, TSH, free T3 and free T4. RESULTS: The mean age of the patients was 15.8±5.7 years. There were 40 (80%) female and 10 (20%) male patients. Ten (20%) patients had positive antithyroid peroxides antibodies and 40 (80%) patients were negative for antibodies. Out of positive serology there were 1 male and 9 female patients. Out of positive serology, 6 patients were having subclinical hypothyroidism, 3 patients overt hypothyroidism and 1 subclinical hyperthyroidism. CONCLUSION: Thyroid disorders are quite high in our type 1 diabetic population. So there is a need to improve screening identiﬁcation among all type 1 diabetics.